Marketing for hospitality and tourism - Kotler, Philip; Bowen, John T.;Makens, James C. (New Jersey : Pearson Prentice Hall, 2006)
ntroductory students and experienced managers alike will find this book a useful tool, providing a strong foundation for hospitality marketing decision-making and know-how ... This book takes an integrative approach to marketing - explaining the how and why of everyone's role in marketing.
Part 1. Understanding the hospitality and tourism marketing process: Introduction, marketing for hospitality and tourism; Service characteristics of hospitality and tourism marketing; Role of marketing in strategic planning -- Part 2. Developing hospitality and tourism marketing opportunities and strategies: Marketing environment; Marketing information systems and marketing research; Consumer markets and consumer buying behavior; Organizational buyer behavior of group market; Market segmentation, targeting, and positioning -- Part 3. Developing the hospitality and tourism marketing mix: Designing and managing products; Internet marketing; Building customer loyalty through quality; Pricing products, pricing considerations, approaches, and strategy; Distribution channels; Promoting products, communication and promotion policy and advertising; Promoting products, public relations and sales promotion; Professional sales -- Part 4. Managing hospitality and tourism marketing: Electronic marketing, Internet marketing, database marketing, and direct marketing; Destination marketing; Next year's marketing plan --
Includes index.
Keywords: HOSPITALITY INDUSTRY -- MARKETING